Morpho-Lexical innovations and socio-political themes in Joe Ushie’s a Reign of Locusts - Maledo, Richard Oliseyenum (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study is based on Joe Ushie’s creative use of the morphological resources of the English Language to realise lexical innovations in his poetry collection A Reign of Locusts (2004). It has been argued that the contact between the English Language and Nigerian indigenous languages is responsible for the innovative use of language in Nigerian literature. However, this paper contends that Nigerian poets in general and Joe Ushie in particular, manipulates the linguistic resources of morphology to realise lexical innovations. The paper considers the creative use of compounding, affixation, blends, lexical hyphenation and lexical bracketing as morphological resources of lexical innovation that are stylistically and thematically motivated. It reveals that Joe Ushie manipulates existing morphological processes to create novel words. It further shows that Joe Ushie’s lexical innovative processes are productive and creative and that the innovative lexical items are nonce formations that have not been integrated into the lexical stock of the English Language. It then suggests that close attention should be paid to such innovative lexis in creative writings in second and foreign language contexts (non-native) as they have the implications for increasing the lexical stock of non-native English in particular and Standard English in general.